2009
DOI: 10.1136/emj.2008.058073
|View full text |Cite
|
Sign up to set email alerts
|

Protocol compliance and time management in blunt trauma resuscitation

Abstract: Results showed the current trauma resuscitation to be ATLS-like, with sometimes very low protocol compliance rates. Timing of secondary survey and radiology and thus time efficiency remains a challenge in all trauma patients. To assess the effect of trauma resuscitation protocols on outcome, protocol adherence needs to be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 27 publications
4
44
1
Order By: Relevance
“…10 Protocol compliance was only 53% when measured pro-spectively using video audit. 11 This lack of compliance with protocols has led experienced trauma care professionals to conclude that "Standardized protocols for resuscitation . .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Protocol compliance was only 53% when measured pro-spectively using video audit. 11 This lack of compliance with protocols has led experienced trauma care professionals to conclude that "Standardized protocols for resuscitation . .…”
Section: Discussionmentioning
confidence: 99%
“…Errors in trauma resuscitation have persisted during the past 20 years despite major improvements in training, facilities, guidelines, and systems of care. [3][4][5][6]10,11 It has been expected that technological developments, along with computer- 12,24,25 It was unclear whether decision support would alter trauma care professionals' behavior in this high-volume facility. It seems unlikely that the reason for poor protocol compliance was lack of awareness of protocols.…”
Section: Commentmentioning
confidence: 99%
“…15 Video review of low-acuity adult trauma resuscitations found that one third of teams failed to expose the patient or make use of warm blankets to prevent hypothermia. 17 Only 3% of these teams measured the patient's temperature, suggesting a lack of focus on this aspect of the resuscitation. Video review of pediatric resuscitations showed that only 11% of trauma teams warmed fluids during bolus administration.…”
mentioning
confidence: 99%
“…Time efficiency remains a continuing challenge during trauma resuscitation and the log roll examination presents an interruption to assessment and management 11 12. In addition, risks to the patient during a log roll manoeuvre and potential musculoskeletal injuries for staff involved have been postulated 13.…”
Section: Introductionmentioning
confidence: 99%